Comparison of molecular with conventional methods for detection of genital tuberculosis in infertile women: A comparative prospective study - Anupama Hari; Anusha Reddy Thota; Sravanthi Katamreddy (Journal of Clinical and Basic Research)
Background: Diagnosis of genital tuberculosis (TB) as a risk factor for infertility remains a diagnostic dilemma for clinicians. Employing the best clinical practices for diagnosing and treating genital TB may help optimize fertility rate. The current study aimed to evaluate the molecular and conventional methods to diagnose genital TB in women with infertility. Methods: A comparative study was conducted on 100 infertile women between 20-35 years of age. Routine laboratory assays and other investigations, such as cervical swab gonorrhea and Chlamydia, Nested TB Polymerase Chain Reaction (TB-PCR), histopathological examination (HPE), culture by Bactec method, and hysterosalpingography (HSG) were performed. Results: The majority of the cases (52%) were between 21 and 25 years. Moreover, 68% of the participants had patent tubes on HSG, 7% had a right tubal block, 9% had a left tubal block, 14% had a bilateral tubal block, and 2% had a unicornuate uterus. Additionally, 9% of the participants were TB-PCR-positive. Hysterolaparoscopy results suggested a likelihood of TB observed among 8% of the participants. Also, 25% of the patients with TB and 7.9% of the patients without genital TB had positive Mantoux test results. Furthermore, 75% of the patients with genital TB had HSG results suggestive of TB, whereas 23.8% of the patients without genital TB had such results. Laparoscopy (75%) and TB-PCR (75%), as well as HSG (75%), were the most specific tests for ruling out genital TB. The most sensitive tests for diagnosing genital TB were TB-PCR (100%), HPE (100%), and laparoscopy (100%). Conclusion: Hysterolaparoscopy is useful for early diagnosis of genital TB. PCR is highly helpful in paucibacillary vaginal TB. Positive findings can be obtained with as few as 10 bacteria/ml of material. In addition to clinical and endoscopic examination, the routine use of endometrial bacteriological PCR testing may be significantly promising for enhancing the diagnosis of genital TB. For the best results, early detection and timely treatment are essential.